2000
DOI: 10.1046/j.1525-1446.2000.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Teleform: A Blessing or Burden?

Abstract: Burgeoning technology has created numerous alternatives for even the most mundane aspect of research, that is, data entry. Our research team is conducting a large NIH NINR clinical trial, and data entry and management are important aspects of this study. Our research team needed to decide whether to use manual data entry or a scannable form of data entry. This article describes some of the advantages and disadvantages related to our decision to use scannable data entry Teleformtrade mark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 1 publication
2
10
0
Order By: Relevance
“…Overall, Tele form ™ was found to be a flexible software package with many potential applications for use in multisite studies. SCRIPT's experience was consistent with that of others who have reported on the use of Tele form ™ and automated data‐form‐processing systems (Davidson et al, 1996; Nies & Hein, 2000; Shiffman et al, 1997). Because of its price, computer expertise required for implementation, and the training required to realize its fullest potential for creating forms, Tele form ™ is not a good solution for small studies (Jorgensen & Karlsmose, 1998) of 100 or fewer participants.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Overall, Tele form ™ was found to be a flexible software package with many potential applications for use in multisite studies. SCRIPT's experience was consistent with that of others who have reported on the use of Tele form ™ and automated data‐form‐processing systems (Davidson et al, 1996; Nies & Hein, 2000; Shiffman et al, 1997). Because of its price, computer expertise required for implementation, and the training required to realize its fullest potential for creating forms, Tele form ™ is not a good solution for small studies (Jorgensen & Karlsmose, 1998) of 100 or fewer participants.…”
Section: Discussionsupporting
confidence: 84%
“…The advantages of these systems lie in their potential to reduce the number of data entry errors, improve the data verification process, and save time (Hammer, Strain, & Lyerly, 1993; Neaton, Duchene, Svendsen, & Wentworth, 1990; Shiffman, Brandt, & Freeman, 1997). Several studies have reported on the use of the Tele form ™ and concur with these advantages (Davidson, Ryan, Rohay, & Sereika, 1996; Nies & Hein, 2000; Puskar et al, 1996; Quan, Vigano, & Fainsinger, 2003). On the basis of these considerations, Tele form ™ was chosen for the data collection and entry system for the Smoking Cessation or Reduction in Pregnancy Trial (SCRIPT) study.…”
mentioning
confidence: 74%
“…According to Velikova et al, 27 there was significant additional work for the research staff who had to check and verify the quality of the database after each scanning of paper forms. Nies et al 28 provided some insights into time utilization of TELEform. They found batch scanning to be best because scanning or faxing, reading, and verifying individual forms was an inefficient process.…”
Section: Discussionmentioning
confidence: 99%
“…All self-report questionnaires were scanned into TeleForm for data entry. 23,24 Data from the accelerometers were uploaded directly from the instruments, and pedometer data were hand-entered by the RAs. Data collected by the accelerometer involved a series of activity counts representing the intensity and duration of motion in the sampling interval (i.e., counts/second).…”
Section: Methodsmentioning
confidence: 99%